Use of industrial brine sludge waste from chlor-alkali industry as a source of sorbent for semi-dry flue gas desulphurisation - Chepkonga, Bilha J. (Vaal University of Technology, 2022)
Stringent antipollution laws have been established to regulate SO2 emissions into the ecosystem. Most power plants in South Africa are fitted with flue gas desulphurisation systems to scrub sulphur dioxide from flue gas(es). Second, to wet scrubbers, spray dry scrubbers (SDS) are gaining prominence due to the generation of a dry product, low water consumption, the robustness of the equipment and high efficiency achieved. Nevertheless, an expensive sorbent (hydrated lime) utilized in SDS raises the overall operational cost of the technique. This study explores the use of sludge generated by a chlor-alkali industry as an alternative source of hydrated lime. Prepared sorbent is then used in a laboratory-scale spray dry scrubber to perform desulphurization test. Characterization techniques sorbent and desulphurisation products was conducted using Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), thermogravimetric analysis-derivative thermogravimetry and scanning electron microscopy(SEM). The effect of process parameters on desulphurisation efficiency and sorbent conversion was investigated. The SO2 removal efficiency of 88.54% was achieved at an inlet temperature of 120°C, sorbent particle size of -45μm, and a Ca:S ratio of 2.5. Calcium conversion decreased with an increase in the Ca:S ratio. Sorbent conversion of 65% was achieved at a gas inlet temperature of 120°C, Ca:S ratio of 1.0 and sorbent particle size of -45μm. The effects of process variables on desulphurisation efficiency using central composite design were also studied. Analysis of numerical optimization revealed that maximum desulphurisation efficiency of 92 % was achieved for particle size of (45-106)μm, an inlet temperature of 140°C, and a Ca:S ratio of 2.0. ANOVA showed that the most significant parameter is Ca:S. A quadratic model was developed to predict desulphurisation efficiency, R2 = 93.47%. Additionally, the effects of highly soluble additives on the performance of prepared hydrated lime in a spray dry scrubber were investigated. The order of additive performance is NaOH> NH4Cl > NH4NO3 > NaCl > Urea. All the investigated additives but urea enhanced the removal efficiency of SO2 above baseline. SO2 content in the model flue gas was reduced by 92.06% and calcium conversion of 54.59% was achieved with 10wt.% Ca(OH) and 8wt.% NaOH which is 45% higher in comparison to the pure sorbent.
M. Eng. (Department of Chemical Engineering, Faculty of Engineering and Technology), Vaal University of Technology.
Keywords: Sulphur dioxide; IBSW - Industrial brine sludge waste; Hydrated lime; Characterization; CCD - Central composite design; Additives; Dissertations, Academic -- South Africa.; Chlorine industry -- Waste disposal -- Environmental aspects -- South Africa.; Alkali industry and trade -- Waste disposal -- Environmental aspects -- South Africa.